ANALISA SISTEM PENGENDALIAN INTERNAL PIUTANG DALAM RANGKA MEMINIMALISASI PIUTANG TAK TERTAGIH PADA PT TUCAN PUMPCO SERVICES INDONESIA - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2015)
The purpose of this study is to determine how much is Internal Control consist of the control environment, risk assesment, control activities, information and communication and monitoring influence to effort of reducing uncollectible accounts at PT. Tucan Pumpco Services Indonesia. Sources of data used in this study is primary data, which are collected by quetionary and straight interviu. This data analyzed by comparing Standart Operating Procedures and result of questionare and interviu in qualitative description. The result of this study showed that the component of Internal Control in PT Tucan Pumpco Services Indonesia are not quite effective to reduce uncollectible account, specially in component monitoring, so company must effort their monitoring activities in way to reducing uncollectible accounts, and so they should have wiser accounting policies for uncollectible accounts. Keywords: Internal Control, Control Environment, Control Activities, Information and Communication, Monitoring, Uncollectible Accounts.